Risk Assessment and Safety Perceptions In The Motorcycle Lane of Butterworth - Kulim Expressway: A Case Study - Mat Saad, Azaruddin; Ab Ghani, Ahmad Raqib (Recent Trends in Civil Engineering and Built Environment, 2026)
Motorcycle lanes have been built at several locations on expresswaysin Malaysia to increase motorcycle safety. The motorcycle lane must have appropriate road safety measures installed to increase road safety, and these measures must be identified and proposed. Previous studies have highlighted the risk of crashes with exclusive motorcycle lanes. There are several factors that contribute to the accidents involving motorcyclist at dedicated motorcycle lanes in Butterworth Kulim Expressway (BKE), Malaysia. Some of these factors include poor road design and inadequate roadside protection. The study aims to accomplish the following goals: evaluating the current state of the motorcycle lane's road safety; identifying and proposing appropriate road safety measures that need to be implemented at the motorcycle lane; and determining how motorcycle riders perceive their level of safety while using the motorcycle lane. To achieve these objectives, the study will conduct field observations to examine the elements of existing road geometry and road facilities. Furthermore, 80 motorcyclist who use the motorcycle lane on the BKE are asked to complete a questionnaire survey to gather statistics. To analyse the data, the study employed the Hazard Identification, Risk Analysis, and Risk Control (HIRARC) method and descriptive analysis (mean and standard deviation test). The study's findings provide insights into the existing risk levels in BKE's motorcycle lanes and recommend suitable road safety measures for enhancement. Furthermore, the research also explores motorcyclists' perceptions regarding the safety standards of these lanes within the BKE.